A Critical Review on Hemicellulose Pyrolysis. Issue 1 (2nd August 2016) - Zhou, Xiaowei; Li, Wenjun; Mabon, Ross; Broadbelt, Linda J.
Abstract: Fast pyrolysis is a promising thermochemical technology that breaks down renewable and abundant lignocellulosic biomass into a primary liquid product (bio‐oil) in seconds. The bio‐oil can then be potentially catalytically upgraded into transportation fuels and multiple commodity chemicals. Hemicellulose is one of the three major components of lignocellulosic biomass and is characterized as a group of cell wall polysaccharides that are neither cellulose nor pectin. The composition and structural features of hemicellulose (mixture of different heterogeneous polysaccharides) and different specific hemicellulose polysaccharides are reviewed. Particular focus is then given to reviewing the status of hemicellulose pyrolysis in terms of experimental investigations, reaction mechanisms, and kinetic modeling. For each aspect, recent results, challenges, and future prospects are addressed. Abstract : Go green, biomass to biofuels : Fast pyrolysis is a promising thermochemical technology that breaks down renewable and abundant lignocellulosic biomass into a primary liquid product in seconds, which can be catalytically upgraded into transportation fuels and multiple commodity chemicals. Here we review the status of pyrolysis of hemicellulose, which is one of the three major components of lignocellulosic biomass. Recent results and challenges as well as future prospects are addressed.